Unsettling colonial modernity in Islamicate contexts - Saffari, Siavash; Akhbari, Roxana; Abdolmaleki, Kara; Hamdon, Evelyn Leslie 1954- (Cambridge Scholars Publishing, 2017)
By focusing on colonial histories and legacies, this edited volume breaks new ground in studying modernity in Islamicate contexts